Prevalence of postnatal depression and associated factors among HIV-positive women in primary care in Nkangala district, South Africa - K Peltzer; M E Shikwane (Southern African Journal of HIV Medicine, 2011)
Background. The prevalence of postpartum depression in South Africa is high, but there is lack of prevalence data on postnatal depression among HIV-infected women.